Performance Measurement, Expectancy and Agency Theory: An Experimental Study - Randolph Sloof; Mirjam van Praag (Tinbergen Institute, 2007)
Theoretical analyses of (optimal) performance measures are typically performed within the realm of the linear agency model. This model implies that, for a given compensation scheme, the agent's optimal effort is unrelated to the amount of noise in the performance measure. In contrast, expectancy theory as developed by psychologists predicts lower effort levels for noisier performance measures. We conduct a real effort laboratory experiment and find that effort levels are invariant to changes in the distribution of the noise term. This suggests that enriching the economic model commonly applied within this area by including an expectancy parameter is not needed.
Keywords: J33; C91; D81; 330; Expectancy theory; agency theory; performance measurement; experiments; Prinzipal-Agent-Theorie; Leistungsanreiz; Leistungsbeurteilung